EVALUATION OF THE COST DRIVERS AND ALLOCATION FRAMEWORK IN OUTBOUND LOGISTICS OF THE FAST-MOVING CONSUMER GOODS INDUSTRY - van Niekerk, Hendrik Johannes; Bean, Wilna (The South African Journal of Industrial Engineering, 2019)
The fast-moving consumer goods industry is a complex trading environment, with many companies experimenting with various ways to increase profit. Outbound logistics, as an integrated concept within supply chain management, remains a key focus area for companies due to the high costs involved. The reality, however, is that often companies do not understand the outbound logistics cost drivers, and hence the profitability of current (let alone new) channels, regions, products, and customers. This is simply due to insufficient information being available from traditional accounting statements. The study evaluates the outbound logistics cost drivers of the South African fast-moving consumer goods industry, and describes an outbound logistics cost allocation framework.